FREE OBJECTS IN A VARIETY OF COMMUTATIVE VECTOR VALUED SEMIGROUPS - Janeva, Biljana (Matematichki Bilten, 1993)
In [5] constructions of free objects in some classes of \((n,m)\)-semigroups are given. In this paper we give a description of a free object with a given nonempty basis in a class of commutative \((n,m)\)-semigroups defined by a system of identities of the form \[ [x_1^p]=[y_1^q], \] where \(p,q>m\) and \((x_1,…,x_p)=(y_1,…,y_q)\).